Pengaruh Pertumbuhan Perusahaan, Ukuran Perusahaan, dan Keputusan Investasi terhadap Nilai Perusahaan pada Perusahaan Sektor Property dan Real Estate - Atika Suryandani (Universitas Muria Kudus, 2018)
Globalization in economics provides an opportunity for every company to enter wider business environment in the face of MEA. The implementation of MEA challenges Indonesian company to seizemarket opportunities in an increasingly competitive business environment. Property and Real Estate sector companies are chosen as the object of research because in 2016 property business sector was among those who were rising. This sector also supports the growth of real sector which is an indicator of the improvement of macroeconomic conditions in Indonesia.This study aims to determine the effect of corporate growth, firm size, and investment decisions on company value. Research object is property and real estate companies listed on the Indonesia Stock Exchange period 3 years 2014 - 2016. Population in this study as many as 40 companies with 19 companies as sample using purposive sampling method. The results of this study indicate that the variable growth of the company affect corporate value; size of the company does not affect the corporate value; while investment decision variables do not affect corporate value.